2000
DOI: 10.1039/b002456m
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three sampling and analytical methods for the determination of airborne hexavalent chromium

Abstract: A field study was conducted with the goal of comparing the performance of three recently developed or modified sampling and analytical methods for the determination of airborne hexavalent chromium (Cr(VI)). The study was carried out in a hard chrome electroplating facility and in a jet engine manufacturing facility where airborne Cr(VI) was expected to be present. The analytical methods evaluated included two laboratory-based procedures (OSHA Method ID-215 and NIOSH Method 7605) and a field-portable method (NI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Furthermore, the website of the National Institute for Occupational Safety and Health (NIOSH) shows various protocols for determining Cr(VI) in environmental air [23], and a comparison of the different analytical methods [24]. The state of the art concerning the measurement of airborne Cr(VI) compounds in workplace aerosols and related samples has recently been reviewed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the website of the National Institute for Occupational Safety and Health (NIOSH) shows various protocols for determining Cr(VI) in environmental air [23], and a comparison of the different analytical methods [24]. The state of the art concerning the measurement of airborne Cr(VI) compounds in workplace aerosols and related samples has recently been reviewed [25].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis with portable UV-vis and UV-vis/NIR spectrophotometers is very simple and despite relatively high detection limits, it is often performed, even for scientific purposes, which can be evidenced by examples of recently published reports (AlmazĂĄn-SĂĄnchez et al, 2014;Dimitroula et al, 2015;Duguma and Walton, 2014;Liu et al, 2014;Meng et al, 2014). Boiano et al (2000) found no statistically significant differences between the results derived from laboratory and field UV-vis spectrophotometric determinations of airborne hexavalent chromium. The mean recovery values were higher for the field method (96.0 712.9% for spiked samples and 98.4 7 6.7% for certified reference material) than for two laboratory based methods (90.4 78.2% and 94.9 76.4% for spiked samples; 84.3 71.9% and 94.2 79.9% for certified reference material).…”
Section: Uv-vis and Uv-vis/near-infrared Portable Spectrophotometersmentioning
confidence: 91%
“…However, for pH between 4 and 5, Cr(VI) reduction into Cr(III) was evidenced [14,15]. Thus, it seems preferable to use more alkaline solutions such as phosphate buffer (pH 8) [16,17,18,19], ammonium/ammonia buffer (8<pH<9) [19,20,21,22], alkaline digestion with a carbonate/sodium hydroxide mixture (pH 12) [23,24,25,26,27], or sodium hydroxide at pH 13 [20,26]. Good extraction recoveries were obtained with the ammonium/ammonia buffer for various pure solid phases such as K 2 CrO 4 (s) or PbCrO 4 (s) [22] and no oxidation of Cr(III) into Cr(VI) was observed for experiments performed with trivalent chromium in the form of Cr 2 O 3 (s).…”
Section: Hexavalent Chromium Extraction From Coatingsmentioning
confidence: 99%